Inebilizumab treatment in a patient with co-occurring AQP4-IgG positive neuromyelitis optica spectrum disorder and myasthenia gravis: a case report and literature review - Song, Xiaoqian; Chen, Jingjiao; Jin, Chenyang; Peng, Yilong; Sun, Yuewen; Zheng, Xueping (Frontiers in Immunology, 2025)
ObjectiveThis study aims to delineate the clinical features underlying the concurrent disease of neuromyelitis optica spectrum disorder (NMOSD) and myasthenia gravis (MG), and to identify efficacious therapeutic strategies.BackgroundNMOSD and MG are uncommon autoimmune diseases that infrequently co-exist. Despite previous reports, a consensus on treating NMOSD concurrent with MG is lacking.MethodsWe present the case of a 55-year-old female with both anti-aquaporin-4 (AQP4) antibody-positive NMOSD and anti-acetylcholine receptor (AChR) antibody-positive MG, who achieved stable disease control following treatment with inebilizumab without significant adverse effects. We also conducted a literature review to evaluate the clinical profile of this comorbidity.ResultsOur review identified 85 patients with concurrent NMOSD and MG. In 70 well-documented cases, MG predated NMOSD in 60 (85.8%) cases, with 42 (70%) patients having undergone thymectomy. Six (8.6%) patients were first diagnosed with NMOSD, and then thymectomy was performed in 2 (33.3%) MG patients. For NMOSD treatment, although most patients received steroid hormones and immunosuppressive agents, quite a few patients had persistent severe disability. Additionally, of 44 patients with clear records of disease recurrence, 31 patients(70.5%) experienced frequent relapses of optic neuritis and myelitis, ranging from 1 to 15 attacks, averaging five. The manifestations of MG are mainly included fatigability, diplopia, and blepharoptosis, with symptoms well-controlled in most patients. Our patient treated with inebilizumab for 1 year and no relapse was recorded to date.ConclusionsThough MG typically precedes NMOSD and thymectomy is frequently performed, it is not a prerequisite for NMOSD development but may represent a potential risk factor. MG generally follows a benign course, in contrast to the more aggressive nature of NMOSD. The utility of biological agents such as inebilizumab for patients with both NMOSD combined with MG warrants further attention.